2002
DOI: 10.1023/a:1019624913037
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Tubercle bacillus was discovered in 1882 by Robert Koch. With the introduction of chemotherapy for tuberculosis in the 1940s the incidence of this entity decreased. The incidence of the tuberculosis of the colon began to increase at the 1980s with the rise in numbers of patients considered as high risk for this entity, such as HIV-infected individuals, patients with chronic renal disease, and immunosuppressed patients with prolonged steroid therapy. We report on two patients with history of chronic abdominal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…In the series by Misra et al 35 10% of patients required surgery for massive lower gastrointestinal bleeding. Similar to previously published series, 11, 21, 35 in our study, the predominant lesions identified on colonoscopy were ulceration and nodularity. The right colon (ileocecal valve, cecum, and ascending colon) was significantly more affected compared with the left.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the series by Misra et al 35 10% of patients required surgery for massive lower gastrointestinal bleeding. Similar to previously published series, 11, 21, 35 in our study, the predominant lesions identified on colonoscopy were ulceration and nodularity. The right colon (ileocecal valve, cecum, and ascending colon) was significantly more affected compared with the left.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to previously reported case series, 11, 21, 35, 39 majority of the patients had non-specific symptoms, with weight loss and abdominal pain being the predominant symptoms in over 80% of the patients. Less than half of the patients in this study had fever.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the 1980s, however, the incidence of extrapulmonary tuberculosis began to increase even in developed countries, with a rise in the numbers of patients considered to be high risk for this disease. This high risk group includes HIV-infected individuals, immigrants from endemic areas, and immunosuppressed patients with transplantations, or who are undergoing prolonged steroid therapy5, 6). Other groups at high risk include alcohol abusers, injection drug users, elderly persons, and diabetic patients7).…”
Section: Discussionmentioning
confidence: 99%